2012
DOI: 10.1155/2012/786839
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Acupuncture and Vagal Regulation

Abstract: Auricular acupuncture has been utilized in the treatment of diseases for thousands of years. Dr. Paul Nogier firstly originated the concept of an inverted fetus map on the external ear. In the present study, the relationship between the auricular acupuncture and the vagal regulation has been reviewed. It has been shown that auricular acupuncture plays a role in vagal activity of autonomic functions of cardiovascular, respiratory, and gastrointestinal systems. Mechanism studies suggested that afferent projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 37 publications
2
135
0
Order By: Relevance
“…With some exceptions, the Chinese charts were very similar to Nogier's originals [12]. Also, according to anatomical studies which suggest that the ear is the only place on the surface of human bodies where there is afferent vagus nerve distribution [13,14], especially in the auricular concha ( Figure 5) [15], a direct stimulation of these afferent nerve fibres on ear supposes to has similar effect to classic VNS without surgical intervention, which is fertile for more disorders (Figure 6) [16]. …”
Section: From Auricular Acupuncture To Transcutaneous Auricular Vagussupporting
confidence: 61%
“…With some exceptions, the Chinese charts were very similar to Nogier's originals [12]. Also, according to anatomical studies which suggest that the ear is the only place on the surface of human bodies where there is afferent vagus nerve distribution [13,14], especially in the auricular concha ( Figure 5) [15], a direct stimulation of these afferent nerve fibres on ear supposes to has similar effect to classic VNS without surgical intervention, which is fertile for more disorders (Figure 6) [16]. …”
Section: From Auricular Acupuncture To Transcutaneous Auricular Vagussupporting
confidence: 61%
“…24 The afferent vagal nerve fibers innervating the tragus area enter the main vagal trunk through the jugular ganglion at level of the skull base. Nomura and Mizuno 25 found that the afferent fibers of ABVN terminated mainly in the nucleus tractus solitaries.…”
Section: Possible Mechanisms Of Ll-ts On Vagus Nervesmentioning
confidence: 99%
“…The underlying mechanisms of auricular acupuncture treatments based on RAMP-uP also will be explored, examining possible neural and/or vascular influences. [31][32][33] Conflict of interest: The authors confirm that there are no known conflicts of interest. …”
Section: Limitation and Future Studiesmentioning
confidence: 68%